Pengaruh Teknik Pelvic Tilt terhadap Intensitas Nyeri Punggung pada Ibu Hamil Trimester III di Puskesmas Karangdoro - Asnia Ananta; Tia Nurhanifah; Mudy Oktiningrum (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Back pain is a common complaint among pregnant women, especially in the third trimester, caused by hormonal changes, uterine enlargement, and poor postural balance. If untreated, this pain can disrupt sleep quality and daily activities. The pelvic tilt technique, a non-pharmacological intervention, strengthens abdominal and pelvic muscles, maintains posture, and relieves back pain. This study examined the effect of the pelvic tilt technique on back pain intensity in third-trimester pregnant women at Karangdoro Public Health Center. The study used a quasi-experimental design with a one-group pretest–posttest approach. The population consisted of all third-trimester pregnant women with physiological back pain (without comorbid conditions or a history of premature rupture of membranes). Using a total sampling technique, 34 respondents were included. The intervention was conducted for seven consecutive days. Data collection employed observation sheets and the Numeric Rating Scale (NRS). Data analysis used the Wilcoxon test because the normality test yielded p < 0.05. Statistical results showed p = 0.000 (< 0.05), indicating that the pelvic tilt technique significantly reduced back pain intensity. These findings suggest that pelvic tilt exercises can serve as a safe, simple, and effective non-pharmacological alternative therapy to alleviate bapain in third-trimester pregnant women.